Is Pest Management getting enough attention in the District Agricultural Development Plan? - Shirur, Mahantesh; Kumar, G. Naveen; Shekara, P. Chandra (Journal of Agricultural Extension Management, 2021)
Compared to any other means of crop losses, the damage caused by the insect pests, diseases and recently the non-insect pests is very serious. Pest Management has not received the attention it merits, in the District Agricultural Development Plan (DADP). The pest and disease management strategies adopted by the farmers are not philosophically based on scientific and rational advisories of the experts, in most cases, especially in cases of pests of serious concern. Many a time, even the advisories by the experts cease to be real-time and location specific, because of the time lag in delivery system or dissemination through unauthorized and unsolicited channels of communication. This policy paper recommends a renewed and vital strategy for addressing this issue and changing the agricultural situation at the district and block level, as pest management has not received enough attention in the District Agricultural Development Plan (DADP)